Post-facial reconstruction maxillary sinusitis associated with aspergillosis: A case report - De Dreyer Da Silva Menezes, J.; Simões Correa, A. P. [UNESP]; Simonetti, L. F.; Stedile Fiamoncini, E.; Capelari, M. M.; Lopes Toledo, G.; Lopes Toledo-Filho, J. (My University, 2014)
Aspergillosis is a term used for fungal infections caused by Aspergillus sp. and mainly affects the airways of adult individuals. The definitive diagnosis of aspergillosis may be difficult, it is commonly confused with chronic sinusitis, but does not recede with the use of antibiotic therapy or irrigation of the maxillary sinus. Rapid intervention is necessary, especially in immunocompromised patients given the fact that this infection slowly progressive is able to cross the barriers and affect important anatomic structures adjacent to the paranasal sinuses with possible orbital and intracranial complications. This paper reports a case of non-invasive fungal sinusitis associated with aspergillosis in a patient with a history of facial fracture treated with reconstruction surgery (reduction and rigid internal fixation). The diagnosis and treatment are discussed, along with clinical, imaging and anatomopathological aspects.
Keywords: Aspergillosis; Maxillary sinus; Mycoses